Criminals, Nazis, and Islamists: competition for power in former Soviet Union prisons - Mironova, Vera (Oxford scholarship online Political Science, 2023)
'Criminals, Nazis, and Islamists' provides an authoritative overview of prisoner organizations in Russia from Soviet times to the present. It shows how the Vory criminal organization, the earliest prison gang, came to dominate Russian prisons over the course of the twentieth century and establish its own unique form of internal prison governance.